MALAYSIAN ESL TEACHERS’ PERCEPTIONS OF THE PRO-ELT PROGRAMME - Nor, Faizah Mohamad; Narodin, Akmal Ariff; Rajab, Azizah; Hamid, Siti Aishah (PEOPLE: International Journal of Social Sciences, 2018)
This article discusses the Pro-ELT programme which addresses the needs of ESL teachers in improving the quality of their teaching. The paper describes the extent of how effective the Pro-ELT programme has been, in preparing teachers of English Language in equipping them with effective teaching skills and enhancing their mastery of the language so as to increase learners’ motivation to learn the English Language and consequently facilitating learners’ mastery of the language. Interviews were conducted with Malaysian school teachers who have already undergone the Pro-ELT training organized by the Ministry of Education for teachers of English. The findings indicated that the training was received well by a few respondents, who found that not only had their teaching skills improved and their confidence to teach increased, but their mastery of the language had also somewhat improved and their learners reportedly enjoyed their lessons more now that their techniques of teaching had undergone improvisations. A few recommendations were given by the teachers on how the Pro-ELT programme can be made more effective in the future.